2010
DOI: 10.1128/jcm.01704-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Clinical Methicillin-Resistant Staphylococcus aureus Isolates in South Africa

Abstract: Eighty-two percent of 320 clinical methicillin-resistant Staphylococcus aureus (MRSA) isolates from various infection sites collected throughout South Africa were separated into five major globally prevalent clusters by SmaI pulsed-field gel electrophoresis, spa, and SCCmec typing. Only one Panton-Valentine leukocidin-positive isolate was detected. This is the first detailed MRSA epidemiology study for the whole country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 16 publications
9
42
1
Order By: Relevance
“…The 100 % susceptibility to GM observed in this study is in agreement with results obtained by Vignaroli et al (2013) who reported a 100 % susceptibility of E. coli isolates from coastal marine sediments to GM. The reemergence of GM-susceptible methicillin-resistant strains of Staphylococcus aureus (MRSA) has been shown in studies conducted in other countries (Sougakoff et al 1998;Blanc et al 2001;Carricajo et al 2001) as well as in South Africa (Essa et al 2009;Marais et al 2009;Heysell et al 2011;Moodley et al 2010). Similar GM susceptibility trends with E. coli observed in this study may indicate the possibility of genetic transfer within the aquatic environment.…”
Section: Prevalence Of Antibiotic-resistant E Coli In Water and Sedisupporting
confidence: 81%
“…The 100 % susceptibility to GM observed in this study is in agreement with results obtained by Vignaroli et al (2013) who reported a 100 % susceptibility of E. coli isolates from coastal marine sediments to GM. The reemergence of GM-susceptible methicillin-resistant strains of Staphylococcus aureus (MRSA) has been shown in studies conducted in other countries (Sougakoff et al 1998;Blanc et al 2001;Carricajo et al 2001) as well as in South Africa (Essa et al 2009;Marais et al 2009;Heysell et al 2011;Moodley et al 2010). Similar GM susceptibility trends with E. coli observed in this study may indicate the possibility of genetic transfer within the aquatic environment.…”
Section: Prevalence Of Antibiotic-resistant E Coli In Water and Sedisupporting
confidence: 81%
“…Certain pandemic MRSA clones are spread worldwide. Recent publications describe the ST612-MRSA-IV clone (MLST CC8) as the most widespread MRSA clone in Cape Town, and South Africa (Jansen van Rensburg et al, 2011;Orth et al, 2013;Oosthuysen et al, 2013;Moodley et al, 2010). In this study ST 612 formed strong biofilms, which may contribute to its dominance in nosocomial infections in South Africa.…”
Section: Discussionmentioning
confidence: 68%
“…CC5 (ST5), CC8 (ST239) and CC30 MRSA clones predominate in Latin America [42]. Recent data from Africa are limited but suggested a predominance of CC8 (ST239 and the infrequently described ST612, found only in South Africa and Australia), CC5 (ST5) and CC30 (ST36) lineages [35,43,44].…”
Section: Hospital-acquired/associated Mrsa (Ha-mrsa)mentioning
confidence: 95%
“…They contain various ST variants (that have point mutations in the genes used for assigning their MLST ST) and are distributed differently in many countries and/or regions of the world. CC22 is widespread globally, CC30-ST36 is common in the USA and the UK and CC45 is common in the USA and Europe [18,28,[33][34][35]. The most frequently reported Asian clones are CC8 (ST239), CC5 (ST5) and CC22 (ST22) [30,[36][37][38][39][40][41].…”
Section: Hospital-acquired/associated Mrsa (Ha-mrsa)mentioning
confidence: 99%